2022
DOI: 10.1101/2022.10.23.513374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

C-4-Modified Isotetrones Prevent Biofilm Growth and Persister Cell Resuscitation inMycobacterium smegmatis

Abstract: Hyperphosphorylated guanosine nucleotide (p)ppGpp, synthesized by Rel proteins, regulates the stringent response pathway responsible for biofilm growth and persister cell formation in the stationary phase of mycobacteria. The discovery of vitamin C as a potent inhibitor of Rel protein activities raises the prospect of such a tetrone lactone to prevent biofilm growth and persister cell formation. The closely related isotetrone lactone derivatives are identified in the present study as potent inhibitors of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…We screened the selected C-4 modified isotetrones (16) (Figure S1) for their potential activity against M. tuberculosis H37Rv by minimum inhibitory concentration (MIC) assay The compounds were screened alone and also in combination with first-line TB drugs. Simultaneously, the selected C-4 modified isotetrones were analyzed for the planktonic growth inhibitory activity against M. tuberculosis H37Rv (Figure S2) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We screened the selected C-4 modified isotetrones (16) (Figure S1) for their potential activity against M. tuberculosis H37Rv by minimum inhibitory concentration (MIC) assay The compounds were screened alone and also in combination with first-line TB drugs. Simultaneously, the selected C-4 modified isotetrones were analyzed for the planktonic growth inhibitory activity against M. tuberculosis H37Rv (Figure S2) .…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we identified the specific bio-enhancer compound that could improve the bactericidal activity of existing TB drugs. As the compound C11 was synthesized by attaching L-phenylalanine to the vitamin C core structure, those could also be regarded as vitamin C analogs (16). The identified bio-enhancer C11 has been shown to have a potent effect in combination with first-line and second-line injectable drugs.…”
Section: Discussionmentioning
confidence: 99%